PERAN GURU PKWU DI SMK MA’ARIF NU KAJEN PEKALONGAN DALAM MEMBANGUN KREATIVITAS DAN PRODUKSI PRODUK INOVATIF - Taufiqoh Khasanah; Finta Nur Febriana; Nadzifah A’isyah Fauzi; Hikma Fitriani; Ferida Rahmawati (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
Teachers of Entrepreneurship Education (PKWU) at SMK Maarif NU Kajen play a vital role in nurturing student creativity and driving the development of innovative products. This qualitative descriptive study explores how PKWU teachers support students in cultivating creativity and producing innovative work. The research identifies three principal roles of teachers: facilitators who use project-based learning and business simulations; mentors who provide academic guidance and emotional encouragement to boost confidence and resilience; and evaluators who assess students’ theoretical knowledge, attitudes, and innovative product outcomes. Key challenges include low student motivation, imbalance between theoretical instruction and practical activities, and insufficient development of soft skills. To overcome these issues, teachers implement strategies such as Project-Based Learning (PBL), integrate digital technologies, and offer continuous mentoring. The findings conclude that successful entrepreneurship education depends largely on teachers’ ability to effectively blend theory with practice, foster a stimulating and enjoyable learning environment, and develop students’ entrepreneurial mindset. This prepares students to become independent, creative, and competitive in the workforce.